A modular optical honeycomb breadboard realized with 3D-printable building bricks and industrial aluminum extrusions. (April 2021) - Toschke, Yannic; Bourdon, Bjoern; Berben, Dirk; Imlau, Mirco
Graphical abstract: Abstract: Optical breadboards with honeycomb structure provide a solid surface with mounting hole grids for building optical assemblies, sub-systems and experiments in the fields of quantum-optics and photonics. Performance criteria are the ability to resist bending under load (stiffness) and the ability to dissipate induced vibrations to the board (damping). The hardware presented in this paper deals with the possibility of assembling optical breadboards using 3D-printed building bricks with honeycomb structure, so-called 'breadboard bricks', and industrial aluminum extrusions, so-called 'breadboard profiles'. With this do-it-yourself approach, it is possible to make changes to the breadboard, such as making an opening, changing its shape or increasing the mounting surface whenever needed. Furthermore, the breadboard is automatically compatible with industrially relevant mechanical design platforms. Aluminum extrusions and the PLA thermoplastic filament provide mechanical stiffness and damping, respectively. Further characteristics are low costs and a modular design. All this makes it especially suited for agile prototyping of (laser) optical assemblies in many engineering processes.